Comparison of immunomodulatory proprieties and antioxidant effect between chicken protein, casein and gluten consumption in mice - Hung, Tran Van; Dung, Pham Khanh; Suzuki, Takuya (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
This study was designed to evaluate the immunomodulatory proprieties and antioxidant effect of chicken protein by comparing with gluten and casein consumption. 18 Six-week-old female Balb/c mice were randomly separated into 3 groups. Without acclimation, mice were fed ad libitum for 8 weeks with AIN-93G (without protein) supplemented with casein or gluten or chicken protein (20% of the total amount) for casein, gluten and meat group respectively. Flow cytometric analysis was used to measure the cell surface expression of CD11b as macrophage marker, and CD11c+ cells in the spleen. In addition, for distinguishing the phenotype of macrophage, ELISA was performed to measure the interferon-ɣ and interleukin-10 in the supernatant of splenocytes cultured with 10μg/mL of concanavalin A. Oxidative stress was evaluated by measuring the total reactive oxygen species generation in liver. For this purpose, the probe, 2’, 7’- dichloro-dihydrofluorescein-diacetate was used, and the result was expressed as fluorescence intensity per mg of protein in the liver homogenate. Regarding the results, splenocytes isolated from mice for each group contained high rate of macrophage, 5.71±0.41%, 5.95±0.47% and 5.24±0.63% for casein, gluten and meat group respectively. Yet, the level of interferon-ɣ and interleukin-10 in the supernatant of splenocytes cultured with concanavalin A for 96h showed no significant differences. In addition, the variation intra-group was a bit high. In fact, interferon -ɣ production was ranged from 30.57 to 162.95 pg/mL, 0 to 122.95 pg/mL and 16.29 to 188.67pg/mL for casein, gluten and meat group respectively. Interleukin-10 production was varied from 7.75 to 185.25pg/mL, 0 to 75.25pg/mL and 0 to 272.75pg/mL for casein, gluten and meat group respectively. Concerning reactive oxygen species generation, no significant difference was also found. However, the trend showed that meat group produced less reactive oxygen species than the 2 other dietary groups. In fact, it was ranged from 0.49±0.03 to 0.96±0.06, 0.68±0.16 to 1.12±0.22 and 0.49±0.08 to 0.74±0.11 fluorescence intensity/mg of protein for casein, gluten and meat group respectively after 40 and 80min of incubation of liver homoginate with DCFDA. Taken together, despite the high rate of macrophage, it was difficult to draw any conclusion about the dominant phenotype in each group. Concerning the antioxidant effect, the trend showed that meat group produces less reactive oxygen species than the other 2 dietary groups.